2004
DOI: 10.1023/b:doop.0000018394.84831.40
|View full text |Cite
|
Sign up to set email alerts
|

Influence of cataract on the multifocal ERG recording – a pre- and postoperative comparison

Abstract: To study the influence of cataract on the multifocal electroretinogram (mfERG), 18 patients underwent mfERG recordings prior to and following cataract surgery. The central 50 degrees of the retina were stimulated by 103 hexagons alternating independently between white and black according to a binary m-sequence. The frame rate was 75 Hz. The maximum luminance was 200 cd/m2, the minimum luminance < 1 cd/m2 with a mean luminance of 100 cd/m2. For each retinal location, the latencies of the first negative peak (N1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 24 publications
3
17
1
Order By: Relevance
“…An early study comparing mfERG topography in different age groups (18)(19)(20)(21)(22)(33)(34)(35)(36)(37), and 48-52 years) showed that P1 amplitude from the central retina (101 in diameter) decreased significantly in the oldest group, 22 but this study did not show changes in N1 amplitude, N1 latency, or P1 latency with increasing age. However, Tzekov et al 29 showed that P1 amplitude and P1 latency decreased with increasing age.…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…An early study comparing mfERG topography in different age groups (18)(19)(20)(21)(22)(33)(34)(35)(36)(37), and 48-52 years) showed that P1 amplitude from the central retina (101 in diameter) decreased significantly in the oldest group, 22 but this study did not show changes in N1 amplitude, N1 latency, or P1 latency with increasing age. However, Tzekov et al 29 showed that P1 amplitude and P1 latency decreased with increasing age.…”
Section: Discussioncontrasting
confidence: 67%
“…As recent studies have found that cataract could reduce mfREG responses, the preretinal optical factors should be noticed. [36][37][38] We believe that previous studies, which showed a significant decrease in mfERG response amplitude and an increase in mfERG response latency, may be due to the confounding effect of media opacities and the instability of fixation. 19,39,40 The different results reported by different studies may be due to different methodologies (eg stimulus luminance and band-pass 41,42 ), assumptions, 19,21 and different criteria for subject inclusion.…”
Section: Discussionmentioning
confidence: 84%
“…228,297,299,315,326 Tam et al studied the effects of different cataract severity on mfERG recordings. 299 It was shown that N1 and P1 response amplitudes from the central macula were significantly reduced in subjects with mild or moderate cataract compared with subjects with very mild cataract.…”
Section: Influence Of Cataract On Mfergmentioning
confidence: 99%
“…228,297 In another study conducted by Wördehoff et al, it was shown that there were significant increases in P1 response amplitudes in the central macula after cataract surgery, while no significant changes in N1 and P1 implicit times were observed. 315 Besides assessing the mfERG changes in cataract patients, studies using artificial light scattering have also been performed to mimic the effects of cataract on mfERG. 8,31,296 Similar to the findings in cataract patients, experimental light scattering resulted in reduction in mfERG responses particularly in the central retina.…”
Section: Influence Of Cataract On Mfergmentioning
confidence: 99%
“…The development of a cataract has a minor influence on the electrophysiological responses, and would reduce the P1 amplitudes in the mfERG [36]. Hypotony maculopathy is the second most common cause of reduction in visual acuity after filtration surgery [34,[37][38][39][40][41], but none of the patients in the current study developed this complication.…”
Section: Discussionmentioning
confidence: 62%